Where to from here - Pettigrew, Simone (Journal of Research for Consumers, 2011)
The Journal of Research for Consumers (JRC) is now 10 years old. It has been an eventful decade. More and more consumer researchers are undertaking consumer-oriented research, either of their own volition or as part of the burgeoning Transformative Consumer Research movement. This article outlines this increase in activity in the context of JRC and the consumer behaviour field more generally. The substantial advances that have been made in human welfare are documented and paralleled with the continued health challenges and other consumption-related issues currently facing humankind. This account highlights the diversity and complexity of these problems and the potential role of consumer researchers in addressing them. As JRC enters its second decade of life, it is hoped that consumer-oriented research continues to increase exponentially and make meaningful improvements to the lives of consumers across the globe.